Seasonality Modulates the Cellular Antioxidant Activity and Antiproliferative Effect of Sonoran Desert Propolis - Pablo Mendez-Pfeiffer; Efrain Alday; Ana Laura Carreño; Jorge Hernández-Tánori; Beatriz Montaño-Leyva; Jesús Ortega-García; Judith Valdez; Adriana Garibay-Escobar; Javier Hernandez; Dora Valencia; Carlos Velazquez (MDPI AG, 2020)
The main chemical composition and pharmacological potential of propolis from arid and semi-arid regions of the Sonoran Desert have been previously reported. Caborca propolis (CP), from an arid zone of the Sonoran Desert, has shown a polyphenolic profile that suggests a mixed plant origin, presenting poplar-type markers, as well as a 6-methoxylated flavonoid, xanthomicrol, characteristic of Asteraceae plants. In addition, CP has shown significant antioxidant properties and antiproliferative activity on cancer cells. In this study, we analyzed the influence of collection time on the chemical constitution, antiproliferative activity and protective capacity of CP against reactive oxygen species (ROS), by using HPLC-UV-diode array detection (DAD) analysis, 3-(4,5-dimethylthiazol-2-yl)-2,5-Dimethyltetrazoliumbromide (MTT) and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assays, as well as cellular antioxidant activity (CAA) assay on murine B-cell lymphoma M12.C3.F6 cells. HPLC-UV-DAD analyses of seasonally collected CP (one-year period) revealed quantitative differences among the most abundant CP constituents: pinocembrin, galangin, chrysin and pinobanksin-3-O-acetate. Though all seasonal samples of CP induced an antiproliferative effect in M12.C3.F6 cells, CP from autumn showed the highest inhibitory activity (IC50: 5.9 ± 0.6 µg/mL). The DPPH assay pointed out that CP collected in autumn presented the highest antioxidant potential (IC50: 58.8 ± 6.7 µg/mL), followed by winter (65.7 ± 12.2 µg/mL) and spring (67.0 ± 7.5 µg/mL); meanwhile, the summer sample showed a lesser antioxidant capacity (IC50: 98.7 ± 2.5 µg/mL). The CAA assay demonstrated that CP induced a significant protective effect against ROS production elicited by H2O2 in M12.C3.F6 cells. Pretreatment of M12.C3.F6 cells with CP from spring and autumn (25 and 50 µg/mL for 1 h) showed the highest reduction in intracellular ROS induced by H2O2 (1 and 5 mM). These results indicate that the antiproliferative effect and cellular antioxidant activity of CP are modulated by quantitative fluctuations in its polyphenolic profile due to its collection time.